2022
DOI: 10.1111/jdv.18146
|View full text |Cite
|
Sign up to set email alerts
|

Use of SEM/EDX methods for the analysis of ambient particulate matter adhering to the skin surface

Abstract: Background The skin is exposed to numerous particulate and gaseous air pollutants. The ones that need particular attention are the particles that adhere to the skin surface, which can later cause direct skin damage. This study aimed to characterize air pollution (AP) particles adhered to the human skin by using scanning electron microscopy (SEM) combined with X‐ray dispersive energy spectrometry (EDX). Methods Tape stripping was performed from six healthy volunteers exposed to urban AP to collect stratum corne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Nonetheless, SEM/EDX can be used to identify and quantify PM 10 in the tear uid. Quantifying particulate matter on Schirmer strips with SEM/EDX may be comparable to methods utilizing skin wipes, which has been used to assess dermal exposure to particulate matter deposition and to estimate air pollution exposure 38 . Biological markers of particulate matter exposure have yet to be reported in human tear uid; however, a study using rat models found that ocular exposure to titanium oxide nanoparticles (a surrogate for particulate matter exposure) induced a signi cant increase in lactate dehydrogenase (p = 0.039) and mucin protein MUC5AC (p = 0.028) in the tear uid 39 .…”
Section: Chemical Markers Of Exposures In the Tear Fluidmentioning
confidence: 99%
“…Nonetheless, SEM/EDX can be used to identify and quantify PM 10 in the tear uid. Quantifying particulate matter on Schirmer strips with SEM/EDX may be comparable to methods utilizing skin wipes, which has been used to assess dermal exposure to particulate matter deposition and to estimate air pollution exposure 38 . Biological markers of particulate matter exposure have yet to be reported in human tear uid; however, a study using rat models found that ocular exposure to titanium oxide nanoparticles (a surrogate for particulate matter exposure) induced a signi cant increase in lactate dehydrogenase (p = 0.039) and mucin protein MUC5AC (p = 0.028) in the tear uid 39 .…”
Section: Chemical Markers Of Exposures In the Tear Fluidmentioning
confidence: 99%
“…Energy dispersive X-ray spectroscopy (EDX) is a technique used for the elemental analysis or chemical characterization of a sample [4]. As a type of spectroscopy, it is based on the investigation of a sample through the interactions between electromagnetic radiation and matter, analyzing the Xrays emitted by matter in response to impact with charged particles.…”
Section: Edx Analysismentioning
confidence: 99%